Colorectal cancer‐susceptibility single‐nucleotide polymorphisms in Korean population. Issue 5 (May 2015) - Hong, Sung Noh; Park, Changho; Kim, Jong‐il; Kim, Duk‐Hwan; Kim, Hee Cheol; Chang, Dong Kyung; Rhee, Poong‐Lyul; Kim, Jae J.; Rhee, Jong Chul; Son, Hee Jung; Kim, Young‐Ho
Abstract Background and Aim Considering the significant racial and ethnic diversity in genetic variation, it is unclear whether the genome‐wide association studies‐identified colorectal cancer (CRC)‐susceptibility single‐nucleotide polymorphisms (SNPs) discovered in European populations are also relevant to the Korean population. However, studies on CRC‐susceptibility SNPs in Koreans are limited. Methods To investigate the racial and ethnic diversity of CRC‐susceptibility genetic variants, we genotyped for the established European CRC‐susceptibility SNPs in 198 CRC cases and 329 controls in Korea. To identify novel genetic variants using genome‐wide screening in Korea, Illumina HumanHap 370K/610K BeadChips were performed on 105 CRC patients, and candidate CRC‐susceptibility SNPs were selected. Subsequently, genotyping for replication was done in 189 CRC cases and 190 controls. Results Among the European CRC‐susceptibility SNPs, rs4939827 in SMAD7 was associated with a significant decreased risk of Korean CRC (age‐/gender‐adjusted odds ratio [95% confidence interval]: additive model, 0.67 [95% CI, 0.47–0.95]; dominant model, 0.59 [95% CI, 0.39–0.91]). rs4779584 and rs10795668 were associated with CRC risk in females and males, respectively. Among candidate CRC‐susceptibility SNPs selected from genome‐wide screening, novel SNP, rs17051076, was found to be associated with a significantly increased risk of microsatellite instability‐high CRC (age‐/gender‐adjusted odds ratio [95% confidence interval]: additive model, 4.25 [95% CI, 1.51–11.98]; dominant model, 3.52 [95% CI, 1.13–10.94]) in the replication study. Conclusions rs4939827, rs4779584, and rs10795668 may contribute to the risk of CRC in the Korean population as well as in European populations. Novel rs17051076 could be associated with microsatellite instability‐high CRC in Koreans. These associations support the ethnic diversity of CRC‐susceptibility SNPs and should be taken into account in large‐scale studies.